(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In order to understand who the Jadids were, it is necessary to know the history of that period very well. Modernism appeared in the late 19th and early 20th centuries. If we want to understand the historical reasons for the emergence of modernism, we need to go a little deeper into history, understand the objective reasons for the backwardness of the Central Asian khanates, which occurred in connection with the weakening of the Great Silk Road in the 16th century, the rise of philosophy and enlightenment in the 19th century. We feel that the ideas of the old-timers are gaining new strength today. We should study our ancient and rich history more deeply, especially the work of our ancestors who boldly raised the ideas of knowledge, human freedom, people’s freedom, love and loyalty to the Motherland and national values in extremely difficult conditions. Their valiant struggle and selflessness towards great goals should serve as a real example school for all of us, first of all, for our youth in building New Uzbekistan.